Composite positive electrode with spatially partitioned transport structure and preparation method and application thereof
Patent Information
- Application Number
- CN202611417379.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-14
- Publication Date
- 2026-10-16
AI Technical Summary
然而,体系结构的替换也带来了新的技术问题:正极电化学反应由传统的气-液-固三相界面反应,转变为结构更为复杂的固-固-气两相界面反应
本发明提供的具有空间分区传输结构的复合正极的制备方法。首先,采用有机酸络合剂辅助溶胶-凝胶法,在三维碳布基底上引入Li3PO4修饰层;随后,通过水热反应,在负载Li3PO4修饰层的碳布表面原位生长Co3O4活性层;最后,经程序升温煅烧处理,使Li3PO4锂离子传导相与Co3O4电催化相在三维碳布骨架上同步结晶生成。通过上述离子传导相预构筑、催化相原位生长、共烧结成型的一体化构建,各组分可实现功能分工:Li3PO4负责锂离子在正极内部的传导,连续碳纤维骨架提供电子传输通路,Co3O4作为活性物质催化ORR/OER反应;纤维之间未被功能组分填满的开放孔隙,则可为氧气扩散以及放电产物的沉积存储提供空间。利用该制备方法所得的具有空间分区传输结构的复合正极包括碳布基底、Li3PO4修饰层和Co3O4活性层;其中,空间分区传输结构以Li3PO4修饰层为离子传输区,以Co3O4活性层为电子传导与电化学反应区,以碳布基底为导电骨架区。利用该空间分区传输结构能够实现不同功能相在同一三维碳布骨架上的空间协同排布,构建起相互匹配的物质传输与电催化反应网络,进而扩大电子、锂离子与氧气三种活性物质共同可达的有效催化反应区域。检测结果表明,本发明提供的有空间分区传输结构的复合正极具有优异的电化学性能,有望在固态锂氧气电池领域得以广泛的应用。
Smart Images

Figure CN122930846A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery electrode materials technology, and in particular to a composite cathode with a spatially partitioned transport structure, its preparation method, and its application. Background Technology
[0002] Lithium-oxygen batteries, using oxygen, electrons, and lithium ions as the positive electrode active materials, possess high theoretical energy density and represent an important research direction in high-energy-density electrochemical energy storage systems. During the battery discharge phase, an oxygen reduction reaction (ORR) occurs at the positive electrode, where oxygen reacts with lithium ions (Li+) that migrate from the negative electrode to the positive electrode. + The combination of electrons and lithium oxide (Li₂O₂) generates solid-state discharge products such as lithium peroxide (Li₂O₂). During the battery charging phase, these solid-state discharge products can decompose at the positive electrode through the oxygen evolution reaction (OER), achieving reversible charge-discharge cycling of the battery. Therefore, the electrochemical reaction at the positive electrode of a lithium-oxygen battery requires electrons and lithium oxide (Li₂O₂). + Simultaneously transported to the catalytic reaction region with oxygen, the cathode needs to have sufficient internal pore space to ensure the smooth generation, deposition, and reversible decomposition of solid-state discharge products.
[0003] Compared to liquid electrolyte lithium-oxygen batteries, solid-state lithium-oxygen batteries use a solid electrolyte instead of the traditional liquid organic electrolyte, effectively improving problems such as evaporation, leakage, and corrosion associated with liquid electrolytes, thus enhancing battery safety and structural stability. However, this structural change also introduces new technical challenges: the positive electrode electrochemical reaction transforms from a traditional gas-liquid-solid three-phase interface reaction to a more complex solid-solid-gas two-phase interface reaction. Solid electrolytes lack the flow and permeation characteristics of liquid electrolytes, making it difficult to fully wet the porous positive electrode structure, thus hindering the development of lithium-ion batteries. + It can only be transported into the interior of the positive electrode through the limited contact area between the solid electrolyte and the positive electrode. This phenomenon will prolong the Li inside the positive electrode to some extent. + The transport pathway and increased solid-solid interface contact impedance prevent many catalytic sites inside the cathode from being fully activated, thus hindering their effective participation in electrochemical reactions and affecting the overall electrochemical performance of the battery.
[0004] Current domestic and international research primarily focuses on improving cathode catalytic activity and optimizing lithium-ion transport performance. While constructing nanostructured catalysts to increase specific surface area or introducing lithium-ion conductive materials can optimize cathode catalytic kinetics and ion transport capabilities to some extent, excessive introduction of various functional components can crowd out the limited pore space of the cathode, negatively impacting oxygen diffusion and transport. It also compresses the deposition space of the solid-state discharge product Li₂O₂, easily leading to pore blockage and decreased catalytic site activity. Therefore, simply optimizing catalytic performance or ion transport performance is insufficient to effectively overcome the current system's technological bottlenecks. Within the limited pore structure of the cathode, rationally controlling the spatial distribution and microstructure of the catalytic, conductive, and ion-conducting phases is crucial for achieving efficient electron-to-lithium transport. + While ensuring efficient and coordinated oxygen transport, reserving suitable pore space to guarantee oxygen diffusion and stable deposition of discharge products is a technical problem that urgently needs to be solved in the field of solid-state lithium-oxygen battery cathodes. Summary of the Invention
[0005] This invention aims to at least solve one of the technical problems existing in related technologies. Therefore, the first objective of this invention is to provide a method for preparing a composite positive electrode with a spatially partitioned transmission structure; the second objective of this invention is to provide a composite positive electrode with a spatially partitioned transmission structure; and the third objective of this invention is to provide applications of the composite positive electrode with a spatially partitioned transmission structure.
[0006] To achieve the first objective, the technical solution adopted by this invention is as follows: A method for preparing a composite cathode with a spatial partitioning transport structure includes: Add the complexing agent to the organic solvent and mix well to obtain an organic solution of the complexing agent; Wherein, the complexing agent is an organic acid complexing agent, and the organic solvent is an alcohol-based polar organic solvent; The lithium salt was added to the organic solution of the complexing agent and mixed evenly to obtain a lithium-ion-containing complex system. Add an aqueous phosphoric acid solution dropwise to the lithium-ion-containing complex system and mix thoroughly to obtain a precursor dispersion system containing Li3PO4 sol; The carbon cloth substrate was immersed in the precursor dispersion system containing Li3PO4 sol, and then subjected to water bath heating and drying treatments to obtain carbon cloth with a Li3PO4 modified layer. The water bath heating temperature is 70–80℃, and the time is 10–25 minutes. The drying process is carried out at a temperature of 45–55℃ for 0.5–1.5 hours. Cobalt salt, ammonium fluoride and urea are added to water and mixed evenly to obtain a precursor reaction solution containing cobalt ions; The carbon cloth with the Li3PO4-modified layer is immersed in the cobalt-ion-containing precursor reaction solution. Under closed conditions, a Co3O4 active layer is grown in situ on the surface of the Li3PO4-modified layer by hydrothermal reaction to obtain an integrated Li3PO4-Co3O4 / carbon cloth composite cathode precursor. After the Li3PO4-Co3O4 / carbon cloth integrated composite cathode precursor is subjected to programmed temperature calcination, a composite cathode with a spatial partitioning transport structure is obtained. The programmed heating calcination process includes a first calcination stage and a second calcination stage. The calcination temperature in the first calcination stage is 195–205℃, and the calcination time is 1–1.5 h. The calcination temperature in the second calcination stage is 340–360℃, and the calcination time is 1.5–2.5 h.
[0007] Preferably, the organic acid complexing agent is selected from any one of citric acid, ascorbic acid, oxalic acid, tartaric acid, malic acid, lactic acid, and acetic acid.
[0008] Preferably, the polar organic solvent is selected from methanol, ethanol, and propanol.
[0009] Preferably, the lithium salt is lithium nitrate and the cobalt salt is cobalt nitrate.
[0010] Preferably, the molar ratio of lithium nitrate to cobalt nitrate is 1:3 to 1:5.
[0011] Preferably, the molar ratio of lithium ions in the lithium salt to the complexing agent in the complexing agent organic solution is 1:(0.9-1.1).
[0012] Preferably, the molar ratio of lithium ions in the lithium-ion-containing complex system to phosphoric acid in the phosphoric acid aqueous solution is (0.9-1.1):1.
[0013] Preferably, the hydrothermal reaction is carried out at a temperature of 85–95°C for 8–10 hours.
[0014] To achieve the second objective, the technical solution adopted by this invention is as follows: A composite cathode with a spatial partitioned transport structure is prepared using any of the above-described methods for preparing a composite cathode with a spatial partitioned transport structure. It includes a carbon cloth substrate, a Li3PO4 modification layer, and a Co3O4 active layer. The carbon cloth substrate is loaded with the Li3PO4 modification layer, and the Co3O4 active layer is grown on the surface of the Li3PO4 modification layer. The Li3PO4 modification layer and the Co3O4 active layer are sequentially composited and coated on the surface of the carbon cloth substrate. The spatial partitioning transport structure uses the Li3PO4 modified layer as the ion transport region, the Co3O4 active layer as the electron conduction and electrochemical reaction region, and the carbon cloth substrate as the conductive framework region.
[0015] To achieve the third objective, the technical solution adopted by this invention is as follows: The application of a composite cathode with a spatial partitioning transport structure is to use the composite cathode with the spatial partitioning transport structure as the cathode of a solid-state lithium-oxygen battery.
[0016] The above-described one or more technical solutions in the embodiments of the present invention have at least one of the following technical effects: This invention provides a method for preparing a composite cathode with a spatially partitioned transport structure. First, an organic acid complexing agent-assisted sol-gel method is used to introduce a Li3PO4 modification layer onto a three-dimensional carbon cloth substrate. Then, through a hydrothermal reaction, a Co3O4 active layer is grown in situ on the surface of the carbon cloth loaded with the Li3PO4 modification layer. Finally, through programmed temperature calcination, the Li3PO4 lithium-ion conducting phase and the Co3O4 electrocatalytic phase are simultaneously crystallized on the three-dimensional carbon cloth framework. Through the integrated construction of the ion-conducting phase pre-construction, in-situ growth of the catalytic phase, and co-sintering, the components can achieve functional division: Li3PO4 is responsible for the conduction of lithium ions within the cathode, the continuous carbon fiber framework provides the electron transport pathway, and Co3O4 acts as the active material to catalyze the ORR / OER reaction. The open pores between the fibers, not filled by the functional components, provide space for oxygen diffusion and the deposition and storage of discharge products. The composite cathode with a spatially partitioned transport structure obtained using this preparation method comprises a carbon cloth substrate, a Li3PO4 modification layer, and a Co3O4 active layer. The spatially partitioned transport structure uses the Li3PO4 modification layer as the ion transport region, the Co3O4 active layer as the electron conduction and electrochemical reaction region, and the carbon cloth substrate as the conductive framework region. This spatially partitioned transport structure enables the spatially coordinated arrangement of different functional phases on the same three-dimensional carbon cloth framework, constructing a mutually matched mass transport and electrocatalytic reaction network, thereby expanding the effective catalytic reaction region accessible to electrons, lithium ions, and oxygen. Test results show that the composite cathode with a spatially partitioned transport structure provided by this invention exhibits excellent electrochemical performance and is expected to be widely used in the field of solid-state lithium-oxygen batteries.
[0017] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Attached Figure Description
[0018] Figure 1 This is a focused ion beam electron beam (FIB) image of a carbon cloth with a Li3PO4-modified layer provided in Embodiment 1 of the present invention.
[0019] Figure 2 This is a projection electron microscope (TEM) image of a carbon cloth with a Li3PO4-modified layer provided in Embodiment 1 of the present invention.
[0020] Figure 3 This is a schematic diagram of the interplanar spacing of the Li3PO4-modified layer provided in Embodiment 1 of the present invention.
[0021] Figure 4 These are scanning electron microscope (SEM) images of a composite positive electrode with a spatial partitioning transmission structure provided in Embodiment 1 of the present invention; wherein, image A is a SEM image with a scale bar of 50 μm and image B is a SEM image with a scale bar of 10 μm.
[0022] Figure 5 This is the elemental distribution diagram of the composite cathode with spatial partitioning transport structure provided in Embodiment 1 of the present invention, obtained by SEM-Energy Dispersive Spectrum (EDS).
[0023] Figure 6 This is a composite positive electrode X-ray diffraction (XRD) spectrum with a spatial partitioning transmission structure provided in Embodiment 1 of the present invention.
[0024] Figure 7 This is a composite positive Fourier transform infrared (FT-IR) spectrum with a spatial partitioned transmission structure provided in Embodiment 1 of the present invention.
[0025] Figure 8 The results are X-ray photoelectron spectroscopy (XPS) test results of the composite cathode with spatial partitioning transmission structure provided in Embodiment 1 of the present invention; wherein, Figure A is the Co 2p spectrum, Figure B is the O 1s spectrum, and Figure C is the P 2p spectrum.
[0026] Figure 9 The images shown are SEM images of the Li3PO4–Co3O4 / carbon cloth composite cathode provided in Comparative Example 1 of this invention; wherein, Image A is a SEM image with a scale bar of 50 μm and Image B is a SEM image with a scale bar of 15 μm.
[0027] Figure 10 This is the SEM-EDS elemental distribution diagram of the Li3PO4–Co3O4 / carbon cloth composite cathode provided in Comparative Example 1 of this invention.
[0028] Figure 11 The images shown are SEM images of the Li3PO4–Co3O4 / carbon cloth composite cathode provided in Comparative Example 2 of this invention; Image A is an SEM image with a scale bar of 50 μm, and Image B is an SEM image with a scale bar of 15 μm.
[0029] Figure 12 This is the SEM-EDS elemental distribution diagram of the Li3PO4–Co3O4 / carbon cloth composite cathode provided in Comparative Example 2 of this invention.
[0030] Figure 13 The images shown are SEM images of the Co3O4 / carbon cloth composite cathode provided in Comparative Example 3 of this invention; Image A is an SEM image with a scale bar of 50 μm, and Image B is an SEM image with a scale bar of 10 μm.
[0031] Figure 14 This is the SEM-EDS elemental distribution diagram of the Co3O4 / carbon cloth composite cathode provided in Comparative Example 3 of this invention.
[0032] Figure 15 This is a cyclic voltammetry curve of the composite positive electrode with a spatial partitioned transport structure prepared in Example 1 of the present invention.
[0033] Figure 16 These are electrochemical impedance spectroscopy spectra of different electrodes provided in the test examples of this invention.
[0034] Figure 17 This is a charge-discharge curve obtained by assembling solid-state lithium-oxygen batteries with different positive electrodes and performing constant current charge-discharge cycles under a current of 50μA, as provided in the test example of this invention.
[0035] Figure 18 This is a capacity curve of a solid lithium-oxygen battery assembled with different positive electrodes, provided by the test example of the present invention, under a current condition of 50μA. Detailed Implementation
[0036] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention. The following embodiments are used to illustrate this invention, but cannot be used to limit the scope of this invention.
[0037] A method for preparing a composite cathode with a spatial partitioning transport structure includes: Add the complexing agent to the organic solvent and mix well to obtain an organic solution of the complexing agent; Wherein, the complexing agent is an organic acid complexing agent, and the organic solvent is an alcohol-based polar organic solvent; The lithium salt was added to the organic solution of the complexing agent and mixed evenly to obtain a lithium-ion-containing complex system. An aqueous solution of phosphoric acid was added dropwise to the lithium-ion-containing complex system and mixed evenly to obtain a precursor dispersion system containing Li3PO4 sol. The carbon cloth substrate was immersed in the precursor dispersion system containing Li3PO4 sol, and then subjected to water bath heating and drying treatments to obtain carbon cloth with a Li3PO4 modified layer. The water bath heating temperature is 70–80℃, and the time is 10–25 minutes. The drying process is carried out at a temperature of 45–55℃ for 0.5–1.5 hours. Cobalt salt, ammonium fluoride and urea are added to water and mixed evenly to obtain a precursor reaction solution containing cobalt ions; The carbon cloth with the Li3PO4-modified layer is immersed in the cobalt-ion-containing precursor reaction solution. Under closed conditions, a Co3O4 active layer is grown in situ on the surface of the Li3PO4-modified layer by hydrothermal reaction to obtain an integrated Li3PO4-Co3O4 / carbon cloth composite cathode precursor. After the Li3PO4-Co3O4 / carbon cloth integrated composite cathode precursor is subjected to programmed temperature calcination, a composite cathode with a spatial partitioning transport structure is obtained. The programmed heating calcination process includes a first calcination stage and a second calcination stage in sequence. The calcination temperature in the first calcination stage is 195–205℃, and the calcination time is 1–1.5 h. The calcination temperature in the second calcination stage is 340–360℃, and the calcination time is 1.5–2.5 h.
[0038] The method for preparing a composite positive electrode with a spatially partitioned transport structure provided by this invention is described in detail below, with the reaction principle and function of each step as follows: I. Alcohol-based polar organic solvents possess excellent polarity and dispersibility, enabling uniform dissolution of complexing agents and effectively avoiding solute agglomeration and precipitation. Organic acid-based complexing agents contain active functional groups such as carboxyl groups, which can provide active sites for subsequent lithium-ion complexation reactions. This system can provide a mild and stable organic reaction environment, laying the foundation for uniform lithium-ion complexation and stable formation of the subsequent sol system, effectively avoiding problems such as uneven particle size and poor coating effect in the subsequent sol.
[0039] 2. Lithium salts are added to the organic solution of the complexing agent and mixed uniformly. Utilizing the coordination effect of the organic acid complexing agent, a reversible coordination complexation reaction occurs between the complexing agent molecules and lithium ions, fixing the free lithium ions within the complexing agent molecular framework. This process improves the uniformity of lithium ion dispersion in the organic system, inhibits localized enrichment and aggregation of lithium ions, and reduces the reactivity of lithium ions. This allows for controllable sol-reaction rates with phosphoric acid, ensuring that the resulting Li3PO4 sol particles are fine and uniform in size, thus guaranteeing the formation of a uniform and dense modified layer.
[0040] Third, an aqueous solution of phosphoric acid is added dropwise to the lithium-ion complex system. Phosphate ions undergo a slow coordination precipitation reaction with the complexed lithium ions in the system, gradually forming Li3PO4 sol particles. Compared to the direct precipitation method, the complexation-based slow-release effect slows down the reaction rate, effectively preventing the rapid aggregation and coarsening of Li3PO4 particles. This gives the sol system excellent stability and adhesion, allowing it to be uniformly adsorbed on the carbon cloth substrate surface, achieving uniform loading of subsequent modification layers. Furthermore, Li3PO4 possesses excellent lithium-ion conductivity, chemical stability, and resistance to electrolyte corrosion, making it a core functional layer for constructing rapid ion transport channels.
[0041] 4. The carbon cloth is immersed in the precursor of Li3PO4 sol. The capillary adsorption of the porous carbon fibers of the carbon cloth is used to fully wet the surface and internal pores of the carbon cloth. Heating in a water bath at 70-80℃ can promote further solidification and cross-linking of the sol particles in a mild liquid environment, enhance the interfacial bonding between the Li3PO4 sol and the carbon cloth substrate, and effectively eliminate residual trace solvents and moisture in the sol system, avoiding subsequent coating peeling and cracking. Low-temperature drying at 45-55℃ can achieve slow dehydration and shaping of the coating. The low temperature condition can avoid coating wrinkles, holes, and cracking defects caused by high-temperature rapid drying. Finally, a uniform, dense, and highly adhesive Li3PO4 modification layer is formed on the surface of the carbon cloth.
[0042] 5. Cobalt salt, ammonium fluoride, and urea are dissolved in water and mixed evenly to prepare a homogeneous precursor reaction solution. Cobalt salt serves as the cobalt source for the Co3O4 active layer, providing the metal ion basis. Ammonium fluoride acts as a mineralizing agent and morphology regulator, adjusting the pH and ion activity of the hydrothermal reaction system to induce the directional growth of the active material. Urea acts as a slow-release precipitant and structure regulator, slowly decomposing to release basic groups and precisely controlling the hydrolysis and precipitation rate of cobalt ions. The synergistic effect of these three agents ensures uniform composition and stable reaction rate in the reaction solution, providing a liquid-phase reaction basis for the in-situ growth of a well-formed and structurally stable Co3O4 active layer.
[0043] VI. A closed hydrothermal reaction system is adopted, using carbon cloth with a Li3PO4-modified layer as a substrate, to grow a Co3O4 active layer in situ on the surface of the Li3PO4-modified layer. The closed hydrothermal environment promotes the uniform hydrolysis, oxidation, and crystallization of cobalt ions. Utilizing the rough interface and active sites of the Li3PO4-modified layer, the active material is directionally attached and grown, effectively avoiding the shedding and aggregation of the active layer. Simultaneously, through a two-step loading process, a spatially layered structure of Li3PO4-modified layer and Co3O4 active layer is formed from the inside out. Li3PO4 is responsible for the rapid conduction of lithium ions and stabilizing the electrode interface, while Co3O4, as the core energy storage active material, provides capacity. The two form a functionally partitioned spatial transport structure, solving the problems of mixed accumulation, hindered ion transport, and poor interface stability in traditional composite electrode materials.
[0044] VII. A two-stage programmed temperature calcination process is used to solidify the crystal structure and optimize the structure of the composite cathode precursor. The first stage, low-temperature calcination at 195–205℃, mainly removes residual moisture, organic solvents, organic complexing agents, and reaction byproducts from the electrode interior at low temperatures, effectively cleaning impurities in the electrode pores. This avoids material structure collapse and coating cracking caused by direct high-temperature calcination, achieving initial structural stabilization of the precursor. The second stage, medium-temperature calcination at 340–360℃, promotes the improvement of the Li3PO4 modification layer's crystal structure and the full crystallization of the Co3O4 active layer, enhancing the material's crystallinity, conductivity, and structural stability. It also strengthens the interfacial bonding between the active layer, modification layer, and substrate, ultimately solidifying to form a stable spatially partitioned transport structure. This allows the high-speed ion transport function of the inner Li3PO4 modification layer and the energy storage function of the outer Co3O4 active layer to be fully utilized, thereby significantly improving the electrochemical performance and cycle stability of the composite cathode.
[0045] In the following embodiments, unless otherwise specified, the experimental methods used are conventional methods, and the materials and reagents used are commercially available, unless otherwise specified, and are carried out in accordance with the techniques or conditions described in the literature in this field or in accordance with the product instructions.
[0046] Example 1 The process for preparing a composite cathode with a spatially partitioned transport structure is as follows: I. Preparation of carbon cloth with Li3PO4-modified layer.
[0047] 0.15 g of citric acid (complexing agent) was dissolved in 10 mL of ethanol (organic solvent), and 0.055 g of lithium nitrate (lithium salt) was added and stirred until completely dissolved to obtain a lithium-ion-containing complex system. Subsequently, 50 μL of an 85 wt% phosphoric acid aqueous solution was added dropwise to this complex system, and stirring was continued for 5–10 min to obtain a precursor dispersion system containing Li3PO4 sol. Then, a 3 cm × 5 cm carbon cloth was immersed in this precursor dispersion system and heated in an 80 °C water bath for 15 min. After the reaction, the carbon cloth was removed and dried in a 50 °C oven for 1 h to obtain the carbon cloth with the Li3PO4-modified layer. Its FIB electron micrograph is shown below. Figure 1 As shown; its TEM electron microscope image is as follows. Figure 2 As shown; its interplanar spacing schematic diagram is as follows. Figure 3 As shown.
[0048] II. Preparation of Li3PO4-Co3O4 / carbon cloth integrated composite cathode precursor.
[0049] Add 40 mL of deionized water to the liner of the reactor, and dissolve 0.58 g of cobalt nitrate, 0.3 g of NH4F and 0.6 g of urea in sequence. Stir until completely dissolved to obtain a precursor reaction solution containing cobalt ions. Immerse the carbon cloth with the Li3PO4 modified layer into the precursor reaction solution, ensuring that the carbon cloth is completely submerged to avoid uneven loading of the Co3O4 precursor due to local exposure. Seal the reactor and react at a constant temperature of 90 °C for 9 h. After the reaction is completed, remove the carbon cloth, wash it repeatedly with deionized water, and then dry it in a 50 °C oven for 6 h to obtain the Li3PO4-Co3O4 / carbon cloth integrated composite cathode precursor.
[0050] III. Li3PO4-Co3O4 / carbon cloth integrated composite cathode.
[0051] The dried composite carbon was arranged in a muffle furnace and heated from room temperature to 200°C at a rate of 2°C / min and held for 1 hour. Then, the temperature was increased to 350°C at the same rate (2°C / min) and held for 2 hours. After natural cooling to room temperature, the carbon was removed to obtain an integrated Li3PO4-Co3O4 / carbon cloth composite cathode, i.e., a composite cathode with a spatial partitioned transport structure. The carbon cloth substrate of this composite cathode is loaded with a Li3PO4 modification layer, and a Co3O4 active layer is grown on the surface of the Li3PO4 modification layer. The Li3PO4 modification layer and the Co3O4 active layer are progressively composited and coated onto the surface of the carbon cloth substrate. The integrated Li3PO4-Co3O4 / carbon cloth composite cathode forms a spatial partitioned transport structure with the Li3PO4 modification layer as the ion transport region, the Co3O4 active layer as the electron conduction and electrochemical reaction region, and the carbon cloth substrate as the conductive framework region. This spatial partitioned transport structure allows different functional phases to form mutually cooperative transport and reaction structures within the same three-dimensional carbon cloth framework, thereby improving the ability to simultaneously acquire electrons and Li. + The ratio of effective catalytic sites for O2.
[0052] SEM images of composite positive electrodes with spatial partitioning transmission structures, such as... Figure 4 As shown; SEM-EDS element distribution map, as follows Figure 5 As shown.
[0053] from Figure 4 and Figure 5It can be seen that a dense cluster of needle-like Co3O4 catalysts is grown in situ on the carbon fiber surface. This unique three-dimensional structure significantly improves the space utilization of the active material and effectively accelerates electron transfer during the reaction process. The needle-like catalyst has a tip diameter of approximately 50 nm and exhibits a dense, uniform, and non-agglomerated porous morphology, thus exposing abundant catalytic active sites and constructing efficient oxygen transport channels. Simultaneously, Li3PO4 introduced into the carbon cloth constructs a complete solid-state lithium-ion transport network, providing a sufficient lithium-ion source for the generation of discharge products. Furthermore, Figure 5 The distribution of Co and P elements further confirms the uniform distribution of needle-like Co3O4 and Li3PO4 on the carbon cloth matrix. These results demonstrate that this embodiment, through the overall coordination of Li3PO4 pre-construction, hydrothermal reaction conditions, and subsequent segmented heat treatment, forms a spatially partitioned transport structure with the Li3PO4 modified layer as the ion transport region, the Co3O4 active layer as the electron conduction and electrochemical reaction region, and the carbon cloth substrate as the conductive framework region.
[0054] XRD patterns of composite cathodes with spatially partitioned transport structures, such as... Figure 6 As shown in the figure, the obvious diffraction peak observed at approximately 24° belongs to the (002) crystal plane of the carbon material. Meanwhile, multiple diffraction peaks appearing at approximately 35°, 44°, 58°, and 64° are highly consistent with the Co3O4 standard card, confirming the successful formation of Co3O4. However, no obvious independent Li3PO4 diffraction peaks were detected in the XRD pattern. Considering the nanoscale loading state of Li3PO4 on the carbon cloth in this embodiment, this phenomenon can be attributed to the small grain size and relatively low content of Li3PO4, as well as the masking effect of the strong diffraction signal of Co3O4 on the carbon cloth substrate.
[0055] FT-IR spectra of composite cathodes with spatially partitioned transport structures, such as... Figure 7 As shown, at 660cm -1 and 562cm -1 The characteristic absorption peak observed at the point is attributed to the stretching vibration of the Co-O bond, further confirming the successful formation of Co3O4 in the composite cathode.
[0056] The detection results of composite positive XPS with spatial partitioning transmission structure, such as Figure 8 As shown; Figure A shows the Co 2p spectrum, with peaks at 779.9 eV and 794.95 eV attributable to Co. 3+ The relevant signals, with peaks at 781.34 eV and 796.86 eV, are attributed to Co. 2+ The relevant signals, along with the corresponding satellite peaks, prove the presence of Co3O4 in the composite cathode. Figure B shows the O 1s spectrum. The peak at 529.98 eV corresponds to the binding energy of the Co-O bond, while the peaks at 531.2 eV and 533.4 eV belong to the binding energy signals related to the phosphorus-oxygen-containing structure in Li3PO4. Figure C shows the P 2p spectrum. The obvious characteristic peak at 33.0 eV corresponds to the P element binding energy signal. Combining the results of the Co 2p, O 1s, and P 2p spectra, it can be confirmed that both Co3O4 and Li3PO4 have been successfully introduced into this composite cathode with a spatial partitioning transport structure.
[0057] Comparative Example 1 I. Prepare carbon cloth with Li3PO4-modified layer according to the method in Example 1.
[0058] II. Preparation of Li3PO4–Co3O4 / carbon cloth composite cathode.
[0059] 0.58 g of cobalt nitrate was dissolved in 50 mL of ethanol, and 0.3 g of citric acid was added. The mixture was stirred until completely dissolved. Carbon cloth loaded with the Li3PO4 precursor was immersed in this solution and heated in an 80 °C water bath until the solvent completely evaporated. The resulting carbon cloth was then dried in a 50 °C oven for 12 h. After drying, it was transferred to a muffle furnace and heated from room temperature to 200 °C at a rate of 2 °C / min and held for 1 h. Then, the temperature was increased to 350 °C at a rate of 2 °C / min and held for 2 h, yielding a Li3PO4–Co3O4 / carbon cloth composite cathode. Its SEM image is shown below. Figure 9 As shown; its SEM-EDS element distribution map, as follows. Figure 10 As shown.
[0060] from Figure 9 and Figure 10 It can be seen that the carbon fiber surface is heavily covered by bulk Co3O4 catalyst, and excessive growth of Co3O4 also occurs in the fiber gaps. This bulk morphology leads to a significant reduction in the specific surface area of the catalyst, thereby weakening its catalytic activity. In addition, the bulk catalyst not only increases the interfacial impedance of the cathode, but also blocks oxygen transport channels and occupies the storage space of reaction products, ultimately leading to a decline in the overall electrochemical performance of the battery.
[0061] This comparative example involved sequentially loading Li3PO4 and Co3O4 precursors onto carbon cloth using a citric acid-assisted method, aiming to simultaneously introduce lithium-ion transport and catalytic components into the cathode. However, during continuous solvent evaporation, the deposition of the Co3O4 precursor was mainly controlled by solvent concentration and localized deposition behavior. The catalyst not only nucleated on the carbon fiber surface but also easily underwent secondary growth on the already deposited catalyst particles, leading to localized agglomeration. These results indicate that a simple sequential loading strategy alone is insufficient to construct a spatial structure conducive to the synergistic transport of multiple substances.
[0062] Comparative Example 2 I. Prepare carbon cloth with Li3PO4-modified layer according to the method in Example 1.
[0063] II. Preparation of Li3PO4–Co3O4 / carbon cloth composite cathode.
[0064] 0.58 g of cobalt nitrate was dissolved in 50 mL of ethanol, and 0.3 g of citric acid was added until completely dissolved. The resulting Li3PO4 precursor carbon was arranged in the above solution and heated in a closed water bath at 80 °C for 9 h. After the reaction was completed, the carbon was dried in an oven at 50 °C for 12 h, and then placed in a muffle furnace. The temperature was increased from room temperature to 200 °C at a rate of 2 °C / min and held for 1 h, and then increased to 350 °C at the same rate (2 °C / min) and held for 2 h to obtain the Li3PO4–Co3O4 / carbon cloth composite cathode. Its SEM image is shown below. Figure 11 As shown; its SEM-EDS element distribution map, as follows. Figure 12 As shown.
[0065] Compared to Comparative Example 1, this comparative example extended the reaction time between the Co3O4 precursor and carbon cloth under sealed conditions, aiming to further regulate the catalyst particle size and its distribution on the carbon cloth. This strategy effectively alleviated the local deposition problem caused by rapid solvent evaporation and improved the oxygen transport space inside the cathode. However, from Figure 11 and Figure 12 It can be seen that the Li3PO4–Co3O4 / carbon cloth composite cathode prepared in Comparative Example 2 failed to fully activate the growth sites on the carbon fiber surface, and a large number of vacant areas still exist. Microscopically, Co3O4 mainly exhibits a blocky structure. Although its particle size and the internal porosity of the carbon cloth were optimized to some extent, a large area of the carbon fiber surface still lacks catalytic structures. Therefore, although this structure retains oxygen diffusion channels, it is limited by the insufficient catalyst specific surface area and carbon fiber surface utilization, resulting in a limited number of effective ORR / OER catalytic active sites.
[0066] Comparative Example 3 40 mL of deionized water was added to the reactor liner, followed by the addition of 0.58 g of cobalt nitrate, 0.3 g of NH4F, and 0.6 g of urea until completely dissolved. Then, carbon cloth was added to the reactor liner, ensuring the solution completely submerged the carbon cloth. The reaction was carried out at 120 °C for 9 h. After the reaction, the carbon cloth was removed and washed with deionized water. The resulting carbon cloth was then dried in a 50 °C oven for 6 h, and then placed in a muffle furnace. The temperature was increased from room temperature to 200 °C at a rate of 2 °C / min and held for 1 h, followed by increasing the temperature to 350 °C at the same rate (2 °C / min) and holding for 2 h, yielding a flower-shaped Co3O4 / carbon cloth composite cathode. Its SEM image is shown below. Figure 13 As shown; its SEM-EDS element distribution map, as follows. Figure 14 As shown.
[0067] from Figure 13 and Figure 14 It can be seen that the Co3O4 / carbon cloth composite cathode prepared in this comparative example forms a flower-like Co3O4 catalytic structure on its surface. Compared with the blocky Co3O4 in Comparative Example 2, the flower-like structure significantly increases the specific surface area of the catalyst and the catalyst coverage on the carbon fiber surface, indicating that the hydrothermal method has a positive effect on controlling the catalyst morphology and improving the space utilization of carbon fibers. However, further observation... Figure 13 It is evident that flower-like Co3O4 not only grows on the surface of carbon fibers but also tends to continue stacking and growing between existing Co3O4 particles. As the size and number of flower-like structures increase, the catalyst gradually extends into the porous regions between adjacent carbon fibers. While this structure increases the geometric specific surface area, it introduces two new problems: firstly, the expansion of the catalyst into the inter-fiber pores compresses the O2 diffusion channels and the storage space for discharge products such as Li2O2; secondly, the electron transport path between some catalysts grown on existing Co3O4 structures and the carbon fiber conductive framework is prolonged, and since this comparative example did not pre-contain a Li3PO4 lithium-ion conducting phase, it becomes difficult for some catalytic regions far from the solid electrolyte interface to continuously obtain Li. + Therefore, Comparative Example 3 illustrates that simply constructing flower-like Co3O4 with high specific surface area to increase catalyst loading and carbon fiber utilization still cannot solve the problems of electron transport and Li. + The synergistic relationship between transport, O2 diffusion, and catalytic area is a concern. Increasing the geometric catalytic area does not mean that all catalytic sites can be converted into effective reaction sites.
[0068] Test Example To investigate the effects of different cathode structures on the reaction kinetics and cycle performance of solid-state lithium-oxygen batteries, cyclic voltammetry, electrochemical impedance spectroscopy, and constant-current charge-discharge tests were conducted on different cathodes. The results are as follows: Figure 15 , Figure 16 , Figure 17 and Figure 18 As shown.
[0069] Figure 15 The figure shows the cyclic voltammetry curve of the composite cathode with spatial partitioning transport structure prepared in Example 1. It can be seen from the figure that the carbon cloth integrated composite cathode exhibits significant redox activity, indicating that it can serve as a highly efficient bifunctional catalyst to effectively promote the ORR / OER reaction kinetics in solid-state lithium oxygen batteries.
[0070] Figure 16 The figures show the electrochemical impedance spectroscopy (EIS) of different electrodes; in the figures, the positive electrodes prepared by the carbon cloth with Li3PO4 modification layer, Example 1, Comparative Example 2, and Comparative Example 3 are respectively labeled as: pure Li3PO4, Li3PO4-acrylic Co3O4, Li3PO4-bulb Co3O4, and flower-like Co3O4. Figure 16 It can be seen that the Li3PO4-Co3O4 / carbon cloth integrated composite cathode obtained in Example 1 exhibits the lowest impedance, indicating that this structure can effectively improve the charge and ion transport processes between the solid electrolyte and the cathode, as well as within the cathode itself; the pure Li3PO4 cathode possesses Li + While capable of transporting components, it lacks Co3O4 active sites that can effectively catalyze the ORR / OER process, thus limiting the interfacial electrochemical reaction kinetics. The Li3PO4-Co3O4 / carbon cloth composite cathode obtained in Comparative Example 2 already contains both Li3PO4 and Co3O4, capable of providing Li... + It possesses transport and ORR / OER catalytic functions, but due to the insufficient utilization of carbon fiber surface and low specific surface area of bulk Co3O4, it is difficult to simultaneously acquire electrons and Li. + The effective catalytic region for O2 remains limited, therefore its impedance is still higher than that of the sample in Example 1. The flower-shaped Co3O4 / carbon cloth cathode obtained in Comparative Example 3 has a higher geometric catalytic area, but no Li3PO4 lithium-ion conducting phase is introduced into the cathode. Furthermore, the flower-shaped catalyst extends into the interfiber pores, affecting the transport of substances within the cathode. The above comparisons demonstrate that having only Li3PO4 and Co3O4 as functional components is insufficient to achieve the superior electrochemical performance of Example 1. The simple coexistence of Li3PO4 and Co3O4 is not a sufficient condition for low impedance; the construction method and spatial distribution of the two functional components in the three-dimensional carbon cloth are also key factors determining the electrochemical performance of the composite cathode.
[0071] Figure 17The figures show charge-discharge curves obtained by assembling solid-state lithium-oxygen batteries using different positive electrodes and performing constant current charge-discharge cycles at 50 μA. In the figures, the positive electrodes prepared from the carbon cloth with a Li3PO4 modified layer, Example 1, Comparative Example 2, and Comparative Example 3 are labeled as: pure Li3PO4, Li3PO4-acrylic Co3O4, Li3PO4-bulb Co3O4, and flower-like Co3O4, respectively. Figure 17 It can be seen that the solid-state lithium-oxygen battery assembled using a pure Li3PO4 cathode exhibits a high initial charge-discharge overpotential and a low capacity, failing to achieve effective cycling within the effective voltage range of 2–4.5V. This is primarily due to the lack of an effective ORR / OER catalyst at the cathode, which significantly limits the kinetics of oxygen reduction and oxygen evolution reactions. In contrast, the solid-state lithium-oxygen battery assembled using the flower-shaped Co3O4 cathode obtained in Comparative Example 3 can achieve a certain number of cycles and has a relatively low initial charge-discharge overpotential, indicating that the flower-shaped Co3O4 can play an ORR / OER catalytic role. However, because a Li3PO4 lithium-ion conducting phase is not introduced into the cathode, and the solid electrolyte cannot fully wet the porous cathode, Li… + The continuous transport of catalytic material into the catalytic region of the cathode is hindered, making it difficult for some catalytic sites to participate in the reaction for an extended period, ultimately leading to premature battery failure. After assembling a battery using the Li3PO4-bulk Co3O4 / carbon cloth composite cathode obtained in Comparative Example 2, the introduction of Li3PO4 improves the internal Li3PO4 transport within the cathode. + Under the transport conditions, its electrochemical performance is improved compared to that of a simple flower-shaped Co3O4 cathode. However, the bulk Co3O4 has a small specific surface area and low coverage utilization of the carbon fiber surface, resulting in insufficient effective ORR / OER reaction area. Furthermore, its high interfacial impedance limits its cycling performance. For the Li3PO4-needle-shaped Co3O4 / carbon cloth integrated composite cathode obtained in Example 1, its unique structural design achieves synergistic optimization of multiphase transport: carbon fiber provides a continuous electron transport network, and Li3PO4 enables Li... +The transport range extends further into the cathode from the solid electrolyte / cathode interface. Co3O4 forms a dense, non-agglomerated needle-like catalytic array on the carbon fiber surface, while abundant loose voids remain between adjacent needle-like structures and carbon fibers, providing ample space for O2 diffusion and the deposition of discharge products. Under the synergistic effect of the functional components and spatial structure, the solid-state lithium-oxygen battery assembled in Example 1 exhibits a low charge-discharge overpotential at 50 μA and successfully achieves 105 effective cycles. In summary, the performance improvement of the composite cathode with spatially partitioned transport structure prepared in Example 1 is not simply due to a single factor among Li3PO4, Co3O4, or the needle-like morphology, but rather the synergistic construction of the Li3PO4 ion-conducting phase, the carbon fiber electron transport framework, the Co3O4 catalytic phase, and the open oxygen transport channels within the same cathode system.
[0072] Figure 18 The figures show the capacity curves of solid-state lithium-oxygen batteries assembled with different positive electrodes under a current of 50 μA. In the figures, the positive electrodes prepared in Example 1, Comparative Example 2, and Comparative Example 3 are labeled as: Li3PO4-needle-shaped Co3O4, Li3PO4-bulb Co3O4, and flower-shaped Co3O4, respectively. Figure 18 It can be seen that the electrochemical performance of the Li3PO4-needle-Co3O4 integrated composite cathode prepared in Example 1 is significantly higher than that of the electrodes obtained in Comparative Example 2 and Comparative Example 3, with a discharge capacity of 3.88 mAh and a charging capacity of 3.37 mAh.
[0073] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a composite positive electrode with a spatial partitioning transmission structure, characterized in that, include: Add the complexing agent to the organic solvent and mix well to obtain an organic solution of the complexing agent; Wherein, the complexing agent is an organic acid complexing agent, and the organic solvent is an alcohol-based polar organic solvent; The lithium salt was added to the organic solution of the complexing agent and mixed evenly to obtain a lithium-ion-containing complex system. An aqueous solution of phosphoric acid was added dropwise to the lithium-ion-containing complex system and mixed evenly to obtain a precursor dispersion system containing Li3PO4 sol. The carbon cloth substrate was immersed in the precursor dispersion system containing Li3PO4 sol, and then subjected to water bath heating and drying treatments to obtain carbon cloth with a Li3PO4 modified layer. The water bath heating temperature is 70–80℃, and the time is 10–25 minutes. The drying process is carried out at a temperature of 45–55℃ for 0.5–1.5 hours. Cobalt salt, ammonium fluoride and urea are added to water and mixed evenly to obtain a precursor reaction solution containing cobalt ions; The carbon cloth with the Li3PO4-modified layer is immersed in the cobalt-ion-containing precursor reaction solution. Under closed conditions, a Co3O4 active layer is grown in situ on the surface of the Li3PO4-modified layer by hydrothermal reaction to obtain an integrated Li3PO4-Co3O4 / carbon cloth composite cathode precursor. After the Li3PO4-Co3O4 / carbon cloth integrated composite cathode precursor is subjected to programmed temperature calcination, a composite cathode with a spatial partitioning transport structure is obtained. The programmed heating calcination process includes a first calcination stage and a second calcination stage in sequence. The calcination temperature in the first calcination stage is 195–205℃, and the calcination time is 1–1.5 h. The calcination temperature in the second calcination stage is 340–360℃, and the calcination time is 1.5–2.5 h.
2. The method for preparing a composite positive electrode with a spatial partitioning transmission structure as described in claim 1, characterized in that, The organic acid complexing agent is selected from any one of citric acid, ascorbic acid, oxalic acid, tartaric acid, malic acid, lactic acid, and acetic acid.
3. The method for preparing the composite positive electrode with a spatial partitioning transmission structure as described in claim 1, characterized in that, The polar organic solvent, an alcohol, is selected from any one of methanol, ethanol, and propanol.
4. The method for preparing a composite positive electrode with a spatial partitioning transmission structure as described in claim 1, characterized in that, The lithium salt is lithium nitrate, and the cobalt salt is cobalt nitrate.
5. The method for preparing the composite positive electrode with a spatial partitioning transmission structure as described in claim 4, characterized in that, The molar ratio of lithium nitrate to cobalt nitrate is 1:3 to 1:
5.
6. The method for preparing a composite positive electrode with a spatial partitioning transmission structure as described in claim 1, characterized in that, The molar ratio of lithium ions in the lithium salt to the complexing agent in the complexing agent organic solution is 1:(0.9-1.1).
7. The method for preparing a composite positive electrode with a spatial partitioning transmission structure as described in claim 1, characterized in that, The molar ratio of lithium ions in the lithium-ion-containing complex system to phosphoric acid in the phosphoric acid aqueous solution is (0.9–1.1):
1.
8. The method for preparing the composite positive electrode with a spatial partitioning transmission structure as described in claim 1, characterized in that, The hydrothermal reaction is carried out at a temperature of 85–95°C for 8–10 hours.
9. A composite positive electrode with a spatial partitioning transmission structure, characterized in that, The composite cathode with a spatially partitioned transport structure, as described in any one of claims 1 to 8, is prepared by means of a carbon cloth substrate, a Li3PO4 modification layer, and a Co3O4 active layer. The carbon cloth substrate is loaded with the Li3PO4 modification layer, and the Co3O4 active layer is grown on the surface of the Li3PO4 modification layer. The Li3PO4 modification layer and the Co3O4 active layer are sequentially composited and coated on the surface of the carbon cloth substrate. The spatial partitioning transport structure uses the Li3PO4 modified layer as the ion transport region, the Co3O4 active layer as the electron conduction and electrochemical reaction region, and the carbon cloth substrate as the conductive framework region.
10. The application of a composite positive electrode with a spatial partitioning transmission structure, characterized in that, The composite cathode with spatial partitioning transport structure as described in claim 9 is used as the cathode of a solid-state lithium-oxygen battery.